The Role of Digital Currencies in Cross-Border Payments and Financial Integration : A Comparative Analysis of Central Bank Digital Currencies (CBDCs) - Krushelnytskyi, Danyil; Abdallah, Kareem Issam; Mammadov, Orkhan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis examines the development and potential impact of Central Bank Digital Currencies (CBDCs) with a focus on their applications in cross-border payments. Analyzing initiatives across Europe and Asia, the study explores how CBDCs could address inefficiencies in the current system. A particular emphasis is placed on offline functionality as a key driver of financial inclusion. The research delves into the delicate balance between user privacy and compliance with Anti-Money Laundering/Combating the Financing of Terrorism (AML/CFT) regulations. The need for harmonized regulatory frameworks and technical interoperability standards to facilitate seamless cross-border CBDC use is highlighted. Finally, the potential of CBDCs to reduce costs, increase transaction speed, and enhance efficiency in international trade is discussed.
Vedoucí práce: Kareem Issam Abdallah
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses